Pemberdayaan Kelompok Usaha Lestari Kulifarm Dalam Budidaya Maggot BSF (Black Soldier Fly) Sebagai Pakan Alternatif Unggas - Rahmawati, Fitri; Sahratullah, Sahratullah; Apriani, Ari; Tanasa, Lala Novela; Abidin, Zainal; Ariani, Laela Azmi (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The community service program for Empowering Novice Community Members (PKM-PMP) conducted by Cordova University involves the Sustainable Labor Group Kuli Farm located in Benete Village, Maluk Subdistrict, West Sumbawa Regency as a partner. The identified issues with the partner include Maggot BSF production and its business management. The methods used in this activity include problem identification, information collection, solution design, training and guidance, mentoring, evaluation, reporting, dissemination of results, and the sustainability of the community service activities. The results of the service activities are evident in the achievement of organic waste counting activities with a realization rate of 100%. The production of a 50 x 100 cm biopon achieved an 80% realization rate. In addition, the creation of labels for Maggot BSF product packaging reached an 80% realization rate. The conclusion drawn is that the implementation of the community service program for Empowering Novice Community Members (PKM-PMP) by Cordova University, in collaboration with the Sustainable Labor Group Kuli Farm, has been successful